An Inexpensive Cardiovascular Flow Simulator for Cardiac Catheterization Procedure Using a Pulmonary Artery Catheter - Johnson, Annika; Cupp, Grace; Armour, Nicholas; Warren, Kyle; Stone, Christopher; Lee, Davin; Gilbert, Nicholas; Hammond, Chris; Moore, John; Kang, Youngbok (Abraham) (Frontiers in Medical Technology, 2021)
Cardiac catheterization associated with central vein cannulation can involve potential thrombotic and infectious complications due to multiple cannulation trials or improper placement. To minimize the risks, medical simulators are used for training. Simulators are also employed to test medical devices such as catheters before performing animal tests because they are more cost-effective and still reveal necessary improvements. However, commercial simulators are expensive, simplified for their purpose, and provide limited access sites. Inexpensive and anatomical cardiovascular simulators with central venous access for cannulation are sparse. Here, we developed an anatomically and physiologically accurate cardiovascular flow simulator to help train medical professionals and test medical devices. Our simulator includes an anatomical right atrium/ventricle, femoral and radial access sites, and considers the variability of arm position. It simulates physiological pulsatile blood flow with a setting for constant flow from 3 to 6 L/min and mimics physiological temperature (37°C). We demonstrated simulation by inserting a catheter into the system at radial/femoral access sites, passing it through the vasculature, and advancing it into the heart. We expect that our simulator can be used as an educational tool for cardiac catheterization as well as a testing tool that will allow for design iteration before moving to animal trials.